Comparison of the In Vitro Bioavailability of Selected Minerals from Gluten-Free Breads Enriched with Grains and Synthetic Organic and Non-Organic Compounds - Anna Rogaska; Julita Reguła; Joanna Suliburska; Zbigniew Krejpcio (Molecules, 2021)
Introduction: Despite the constant efforts of scientists to improve the texture, sensory properties, and nutritional value of gluten-free bread, obtaining high bioavailability of minerals is still a huge challenge. Gluten-free bakery products are characterized by a low bioavailability of minerals. The aim of this study was to design gluten-free bread with high bioavailability of minerals commonly found in deficiencies in people struggling with gluten intolerance. Material and methods: The material consisted of gluten-free breads designed to obtain the highest possible content of minerals in the bread while maintaining a good structure and taste. Results: Higher contents of all the analyzed minerals were obtained in breads with natural and synthetic additives, both in rice and buckwheat bread, compared to basic bread. There was also a higher content of the analyzed minerals in buckwheat bread in comparison to rice bread for each type of additive. Higher bioavailability of iron, copper, calcium, and magnesium was noted in rice bread, while the bioavailability of zinc was higher in buckwheat bread. Conclusion: The additives used increased the bioavailability of the analyzed minerals from the gluten-free breads. The use of various variants of flour (rice, buckwheat) influenced the bioavailability of iron, zinc, copper, calcium, and magnesium. The release of minerals from gluten-free bread depends on the element and added components (seeds or synthetic additives).